ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
This study aimed to analyze students' critical thinking skills through the implementation of guided inquiry learning model on salt hydrolysis lesson. The research design used in this study was One-Shot Case Study. There were 79 students taken as the subjects of this study and they were in eleventh grade majoring MIPA of SMAN 2 Brebes in academic year 2017/2018. A test instrument that have been proven to be valid by expert were used to figure out both students’ critical thinking skills and obtained reliabelitas of 0.96 by using the formula r11 (alpha cronbach). The results showed the percentage of achievement students' critical thinking ability of 86.18% including good category. Percentage of achievement of each indicator of Critical Thinking Capability (KBK): simple explanation, 81,4%, basic support 85,95%, inference 87,31%, and stategies and tactics 87,34%. Students respond positively to the learning that has been applied.
Keywords: Critical Thinking Skills; Guided Inquiry